Anaesthesia modalities during laser photocoagulation for retinopathy of prematurity: a retrospective, longitudinal study. Issue 1 (24th January 2017) - Jiang, Jing-bo; Strauss, Randy; Luo, Xian-qiong; Nie, Chuan; Wang, Yan-li; Zhang, Jia-wen; Zhang, Zhi-wei
Abstract : Objectives: Laser photocoagulation surgery is a routine treatment for threshold retinopathy of prematurity (ROP). However, little is known about which anaesthesia protocols provide efficient pain control while minimising exposure risk to vulnerable infants. In this study, therefore, we assessed the efficacy and tolerability of multiple anaesthesia techniques used on premature infants during laser therapy. Design and main outcome measures: Anaesthesia modalities consisted of topical eye drops anaesthesia, general anaesthesia and intravenous fentanyl sedation with mechanical ventilation. Laser treatment efficacy and detailed operative information were retrospectively and consecutively analysed. Cardiorespiratory stability was assessed and compared. The Neonatal Pain Agitation and Sedation Scale (N-PASS) was used to evaluate tolerability in infants that underwent intravenous fentanyl sedation. Results: 97 cases of prematurity were included in this study. In 94/97 (96.9%) cases, vascular proliferation regressed. In the topical anaesthesia groups, the ophthalmologist needed 12–16 min more to complete the treatment. During the 3 postoperative days, topical anaesthesia demonstrated the greatest instability; 4/31 (12.90%) infants in this group suffered from life threatening events requiring resuscitation. The only instability observed in general anaesthesia and fentanyl sedation was attributed to difficulty in extubating within 24 hours after surgery. During laser therapy, the N-PASS score increased to 1.8 in the fentanyl sedation group. Conclusions: Topical anaesthesia was associated with more cardiorespiratory instability during ROP laser treatment. While general anaesthesia and fentanyl sedation had similar postoperative cardiorespiratory results, the latter demonstrated acceptable pain stress control. However, the difficulty of weaning off mechanical ventilation in some cases after surgery needs to be addressed in future studies.